Overview of SARS-CoV 2 infection case and fatality descriptive analysis in Samarinda, East Kalimantan 2020-2021 - Gusrina, Sylvia (BKM Public Health and Community Medicine, 2021)
Objective: The study provides an overview of Covid-19 cases in Samarinda City since the Pandemic started in March 2020 until the third quarter of 2021, immediately after the peak of the second wave. Content: Samarinda is the capital city of East Kalimantan, one of the top ten provinces with the highest number of Covid-19 cases in Indonesia. The study extracted data from the Covid-19 national notification system application called Allrecord TC-19 di Indonesia. Overall, 22.152 or 2664,9 cases per 100.000 population were reported, while the peak of the second wave reached 1516 cases in the 28th epidemiology week of 2021, which was tripled the number of the first wave. Case Fatality Rate (CFR) was 3,22% with the highest death reaching 67 cases in a week. 54,2% of SARS CoV-2 Infection occurred in men with a 3,4% fatality rate, while in women it was 3,0%. Almost half (47,5%) of the total cases affected the productive age group (20-40 years old age group). Meanwhile, the most Case Fatality Rate (CFR) occurred in the elderly age group, with 233 cases (1,06%) affecting people in their 50s-60s and 202 cases (0,91%) in their 60s-70s. Based on location analysis, the highest number of cases was found in Samarinda Ulu subdistrict with 15,02% (4162 cases). However, the highest Attack Rate(AR) occurred in Samarinda Kota subdistrict with 4032,41 cases per 100.000 population, while the proportion is only 5,8% from total cases. The highest CFR is 6,17% which occurred in the Samarinda Ilir subdistrict. Uniquely, the number of cases reported by the settler was about 8,57% which was higher than the other six subdistricts (5,11% - 6,11%). Further analysis is needed to explore risk factors and causal relationships between the factors and the Covid-19 case in Samarinda City to produce recommendations that can strengthen Covid-19 prevention and control efforts by all sectors.